KRETERIA DESAIN FOTOBIOREAKTOR SISTEM AIRLIFT REACTOR - Santoso, Arif Dwi; H.S, Abdil; ., Diyono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Global warming has become an increasingly important issue around the world today dueÃ‚Â to the rise of anthropogenic greenhouse gases emission, which gives several negativeÃ‚Â impacts on human life.Ã‚Â There are some techniques have been studied and assessed i.e. physical mechanismÃ‚Â by injected CO2 to the geological formations, chemical mechanism with artificial treeÃ‚Â technology and biological mechanism by increasing the primary production throughÃ‚Â iron enrichment in high nutrient-low chlorophyll (HNLC) waters as well as mixing ofÃ‚Â water column below the sea surface. Those technologies, which are well known asÃ‚Â Carbon Capture Storage Ã¢â‚¬Ëœ(CCS) technology, are expected to be applied to reduceÃ‚Â the oncentration of anthropogenic CO2 in the atmosphere and to minimize the globalÃ‚Â warming.Ã‚Â The Center of Environmental Technology, Agency for the Assessment and Application ofÃ‚Â Technology (BPPT) will carry out a research concerning CO2 reduction by a phytoplanktonÃ‚Â culture in a photobioreactor in three years. The main objective of this research is toÃ‚Â assess the CO2 uptake capability of tropical phytoplankton.Ã‚Â In this paper, we would showed the creteria and design to assembly a photobioreactorÃ‚Â esspesially a air lift photobioreactor. To improve performance photobioreaktor, theÃ‚Â materials included design criteria and the dynamics of fluids in fotobioreaktor have toÃ‚Â considered propoerly. Other the hand, the selection of the most productive species andÃ‚Â selection of appropriate media and economically also important to be done.Ã‚Â Keywords: global warming, creteria and design, greenhouse gas, air lift photobioreactor